Teaching NeuroImage: Non–24-Hour Sleep-Wake Rhythm Disorder. (31st May 2022) - Tesson, Alan R.; Ali, Mir Mustafa; Spector, Andrew R.
Abstract : A 77-year-old woman with obstructive sleep apnea reported a lifelong difficulty with periods of severe nocturnal insomnia and daytime sleepiness. Wrist actigraphy, the diagnostic method of choice for circadian rhythm disorders, was not covered by insurance. A review of her CPAP data (Figure) demonstrated progressively later bedtimes with a period of greater than 24 hours, revealing the diagnosis of non–24-hour sleep-wake rhythm disorder. While common in unsighted individuals, non–24-hour sleep-wake rhythm disorder can occur in sighted people, 1, 2 as was the case here. For patients on PAP therapy, adherence data can provide evidence of circadian rhythm disorders.